2013
DOI: 10.1603/me12206
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Malaria Vector Control Interventions: Effectiveness of Five Different Adult Mosquito Sampling Methods

Abstract: Long-term success of ongoing malaria control efforts based on mosquito bed nets (long-lasting insecticidal net) and indoor residual spraying is dependent on continuous monitoring of mosquito vectors, and thus on effective mosquito sampling tools. The objective of our study was to identify the most efficient mosquito sampling tool(s) for routine vector surveillance for malaria and lymphatic filariasis transmission in coastal Kenya. We evaluated relative efficacy of five collection methods—light traps associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 54 publications
(90 reference statements)
0
34
1
Order By: Relevance
“…We used the following trap models: New Standard Miniature BlackLight (UV) Trap (Model 1212 John Hock Company, Gainesville, FL), CDC Mini Light Trap with Incandescent Light (Model 2836BQ Bioquip Products, Rancho Dominquez, CA), and CDC Gravid Trap (Model 1712, John Hock Company, Gainesville, FL). We used both CDC light traps and Miniature Blacklight (UV) traps interchangeably, due to the availability of traps in Galapagos and since both traps attract host‐seeking mosquitoes (Chun‐Xiao et al , Onyango et al ). Light traps were baited with a CO 2 ‐emitting sugar/yeast/water mixture (250 g/ 35 g /2.5 liters, respectively) (Smallegange et al ), which has been shown to increase both catch numbers and diversity, while making the specific trap location less critical (Silver and Service ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the following trap models: New Standard Miniature BlackLight (UV) Trap (Model 1212 John Hock Company, Gainesville, FL), CDC Mini Light Trap with Incandescent Light (Model 2836BQ Bioquip Products, Rancho Dominquez, CA), and CDC Gravid Trap (Model 1712, John Hock Company, Gainesville, FL). We used both CDC light traps and Miniature Blacklight (UV) traps interchangeably, due to the availability of traps in Galapagos and since both traps attract host‐seeking mosquitoes (Chun‐Xiao et al , Onyango et al ). Light traps were baited with a CO 2 ‐emitting sugar/yeast/water mixture (250 g/ 35 g /2.5 liters, respectively) (Smallegange et al ), which has been shown to increase both catch numbers and diversity, while making the specific trap location less critical (Silver and Service ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Onyango et al . () found that the Prokopack was more suitable for the collection of indoor resting Culex quinquefasciatus (Diptera: Culicidae) than methods using pyrethrum spray catches, clay pots or urine‐baited traps. Like Maia et al .…”
Section: Introductionmentioning
confidence: 95%
“…(), Onyango et al . () caught too few anophelines to undertake such a comparison for this genus. Thus, although it is becoming a standard method for the collection of resting mosquitoes (Killeen et al ., ), the Prokopack's efficacy in collecting anophelines has yet to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…These traps often use an attractant (such as carbon dioxide [CO 2 ]) to lure and capture host-seeking female mosquitoes seeking a blood meal. Human landing rates monitor actively biting mosquito populations, but the ethical soundness of such methods is debatable in known high-risk regions (Krockel et al 2006, Trout et al 2007, Onyango et al 2013. To collect gravid mosquitoes, gravid traps are baited with bacteria-, grass-, or oak (Quercus)-water or other infusions Gingrich 2007, Obenauer et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To collect gravid mosquitoes, gravid traps are baited with bacteria-, grass-, or oak (Quercus)-water or other infusions Gingrich 2007, Obenauer et al 2010). Resting boxes and resting traps collect bloodfed mosquitoes that rest on the sides of walls or on vegetation (Panella et al 2011, Onyango et al 2013; clay pots are used to monitor resting mosquitoes in Africa (Odiere et al 2007). Immature mosquitoes are often collected via dipping in stagnant bodies of water (Almiron and Brewer 1994) or setting out ovitraps consisting of artificial containers (plastic cups) baited with water and lined with seed germination paper on which mosquitoes may oviposit (Krockel et al 2006, Trout et al 2007.…”
Section: Introductionmentioning
confidence: 99%